(untitled) (Eurasian Journal of History, Geography and Economics, 2025)
The article describes the tax policy in Uzbekistan during the Second World War in the direction of the military needs of all industries, the subordination of the tax system to the interests of war, increasing the financial power of the state and strengthening the budget system. Attention is also focused on the centralization of tax collection and some tax benefits, the mandatory payment of taxes that took place in difficult and difficult conditions during the war.